Mental arithmetic in the development of intellectual abilities: searches and results. (Journal of Educational Sciences, 2017)
The authors justify the necessity of development of intelligence in primary school children with the help of mental arithmetic. Noting that the complex development of children’s intelligence in the early school agegoes in several different directions (absorption and active use of speech as a tool thinking, connection and impact of each other all kinds of thinking, etc.), the authors refer to the possibility of mental arithmetic to complex function used two hemispheres of the brain. In the main part of the article the authors present the results of the mini-study conducted among primary school children visiting the center of intellectual development “Advanced.” The essence of the mini-study was to identify how do intellectual and creative abilities develop in children during the lessons of mental arithmetic. Rising interest rates intellect, photographic memory and fine motor skills, as well as the decline in creative thinking and focus of this group of students, say on the effectiveness of training of mental arithmetic to form the intellectual development and the need for further study of the problem, as well as the development of methodological basis for its application.
Keywords: mental arithmetic; the development of intelligence; creativity abilities; intellectual abilities